Effect of Toothbrushing Simulation Method with Bass Technique on the Dental and Oral Hygiene - Inayatur Rosyidah; Iva Milia Hani Rahmawati (Babali Health, 2021)
Introduction: Toothbrushing practice is a common problem encountered in maintaining children's dental and oral hygiene. The Bass Technique introduces to improve the practice of toothbrushing and promotes dental/oral hygiene among school-aged students. This study aimed to know the effect of the toothbrushing simulation method with bass technique on the dental and oral hygiene practice in Pulo Lor III Elementary School. Methods: This was a pre-experimental study with one group pretest-posttest design. The study population was 49 students aged between 7 to 10 years old in Pulo Lor III Elementary School. Thirty students selected for the study by the purposive sampling technique. The independent variable was the toothbrushing method with the bass technique, while the dependent variable was dental and oral hygiene. An observation sheet and OHI-S questionnaire were employed to collect the study data. The Wilcoxon signed-rank test used to analyze the study data collected. Results: The result revealed after the implementation of the bass technique, the number of participants with poor practice of dental and oral hygiene was increasing by a total of 0 (0%), followed by good and moderate practice of oral hygiene with a percentage of 13 (43.3%) and 17 (56.7%), respectively (p=0.000). The dental and oral hygiene observed after and before the implementation of the bass technique was also significant, with the value of p of 0.000. Conclusion: Toothbrushing with bass technique significantly affected the dental and oral hygiene among students aged between 7 to 10 years old in Pulo Lor III Elementary School, Jombang District.